Makna Simbolik Rumah Adat: Analisis Semiotika pada Komunitas Towani Tolotang - Aska, Aulya Milatul; Miftahudin, Istih Ainun Sa'adah; Arkam, Andi Iksan; Fauzan, Fakhri (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2025)
This study is motivated by the limited in-depth research on the symbolic meanings embedded in the architecture of the Towani Tolotang traditional house. Therefore, this research aims to reveal the meanings contained in the architectural elements and ornaments of the traditional house. The study employs Charles Sanders Peirce’s semiotic theory as the analytical framework, using a qualitative research method with an ethnographic approach. Informants were selected through purposive sampling and consisted of three individuals knowledgeable about Towani Tolotang traditions. Data were collected through interviews, observation, and documentation. The findings show that the Towani Tolotang traditional house, particularly the homes of traditional leaders (Uwa’), contains strong symbolic meanings in each of its architectural features. The three-tiered stilt-house structure represents Bugis mythological concepts; the round or twelve-sided pillars symbolize the steadfastness of Tolotang ideology; the bamboo flooring ensures smooth air circulation; the odd number of steps is believed to bring good fortune to the homeowner; the tamping reflects respect toward the Uwa’ as traditional leaders; the white color signifies purity; the use of wood for doors and windows embodies respect for nature; and the carvings symbolize hopes for a prosperous life. These findings imply that the Towani Tolotang traditional house functions not only as a physical dwelling but also as a medium for preserving the spiritual, cultural, and philosophical values of the Tolotang community, highlighting the importance of safeguarding and introducing it as part of local cultural heritage preservation efforts.